Impact of single‐session motivational interviewing on clinical outcomes following periodontal maintenance therapy. Issue 2 (24th December 2012) - Brand, VS; Bray, KK; MacNeill, S; Catley, D; Williams, K
Abstract Objectives Patient engagement in effective oral hygiene following periodontal therapy is essential to long‐term success. Motivational interviewing (MI) is a behavioural counselling approach documented to positively influence behaviour change related to smoking, diabetes control and medication adherence. Emerging evidence suggests utility of MI to improve oral health. The objective of this study was to evaluate whether the use of brief motivational interviewing (BMI) is effective in improving internal motivation for oral hygiene behaviour. Methods A convenience sample of fifty‐six previously treated periodontal patients who were in maintenance yet presented with signs of clinical inflammation were recruited to participate in this single blind, randomized controlled trial. Patients were randomly assigned to receive either BMI in conjunction with traditional oral health education (TOHE), (n = 29) or TOHE alone (n = 27). Bleeding on probing scores (BOP), plaque index (PI), pocket depths (PD), motivation (M), autonomous regulation (AR) controlled regulation (CR) and oral health knowledge (K) were assessed at baseline, 6 weeks and 12 weeks. Results Statistically significant decreases were found over time for BOP (P = 0.001), PI (P = 0.001) and PD 4–6 mm (P = 0.001) for both groups. Differences in clinical parameters between groups were not evident at either 6 or 12 weeks. Conclusion Results show that a one‐time MI session is insufficient for improving oral hygiene in long‐standing maintenance patients.